Measurement of intrinsic foot stiffness in minimally and traditionally shod runners using ultrasound elastography: A pilot study - Bell, E. A.; Hibbert, J. E.; Domire, Z. J. (Journal of Sports Sciences, 2020)
Running is an activity with a consistently high injury rate. Running footwear design that mimics barefoot running has been proposed to reduce injury rate by increasing the strength of foot structures. However, there is little evidence to support this. The purpose of the current study is to use shear wave ultrasound elastography to examine material properties (shear modulus) of intrinsic foot structures in experienced minimally and traditionally shod runners. It is hypothesized that minimalist runners will exhibit increased stiffness compared to controls demonstrating the strengthening of these structures. Eighteen healthy runners (8 minimalist and 10 traditionalist), running a minimum of 10 min/wk, participated. Elastography scans were performed on the left foot of each participant. There is no apparent stiffening of foot structures associated with wearing minimalist shoes. Only the FHB tendon is different between shoe types and, contrary to the hypothesis, was stiffer in traditionalist compared to minimalist runners (257.26 ± 51.64 kPa vs 160.88 ± 27.79 kPa, respectively). A moderate positive (r = 0.7) relationship between training load and tendon stiffness suggests strengthening of tendon when running in traditional shoes. If running in minimalist shoes increases loading on these structures without resulting in stronger tissues, it is possible that minimalist footwear may increase injury risk.